The IBA Guidelines on Party Representation in International Arbitration : A Guide - Ashford, Peter (Cambridge : Cambridge University Press, 2016)
The guidelines on party representation are one of three key publications published by the IBA and are commonly referred to or adopted as good practice in international arbitration. This user-friendly handbook to the guidelines will benefit the understanding and practical application of arbitration protocol in the legal community. Written by a respected and experienced arbitration practitioner, this is a companion volume to The IBA Rules on the Taking of Evidence in International Arbitration and combines commentary from the drafting committee, additional analysis of the guidelines and tabular comparative material addressing the interaction with Major Professional Conduct Rules and Major Institutional Rules. It is a convenient and invaluable resource for best practice on the duties of arbitrators, institutions and other representatives in this field.
Title from publisher's bibliographic system (viewed on 03 May 2017).